RNA interference therapeutics for cancer: challenges and opportunities - Bora, R.; Gupta, D.; Mukkur, Trilochan; Saini, K. (Spandidos Publications, 2012)
Abstract. RNA interference (RNAi) is a sequence-specific, post-transcriptional gene silencing mechanism in animals and plants, which is mediated by double-stranded RNA (dsRNA). There has recently been an increasing interest in harnessing the gene silencing activity of dsRNA to develop novel drugs for the treatment of various diseases, such as cancer, neurological disorders, age-related macular degeneration and viral infections. Small interfering RNA (siRNA)-based drugs have distinct advantages over conventional small molecule or protein-based drugs, including high specificity, higher potency and reduced toxicity. However, there are several technical obstacles to overcome before siRNA-based drugs reach the clinic. Delivery of siRNA to the target tissues and stability in the serum remain a major challenge and are the main focus of current research and development efforts. This review focused primarily on the progress made in developing RNAi as therapeutics for cancer and the challenges associated with its clinical development. Use of ligands recognizing cell-specific receptors to achieve tumor-specific delivery of siRNA, methods for enhanced siRNA delivery, improving the bioavailability and pharmacokinetic properties of siRNA and reducing the off-target effects and non-specific gene silencing are discussed in the light of current evidence.